(untitled) (Research, Society and Development, 2025)
Cassava is one of the main crops cultivated in the North and Northeast regions of Brazil. It is a highly important plant for food security and is considered by many as a subsistence crop due to its ability to withstand various climatic adversities and soil conditions. As a result, it can be grown almost anywhere, making it a crop found in all Brazilian states. Therefore, understanding the insects associated with this crop is essential, especially when they are pests capable of causing damage. The objective of this study was to report the first record and assess the occurrence of the stem borer in cassava crops in the states of Rondônia and Amazonas. The occurrence of the stem borer, Chilomima clarkei (Amsel, 1956) (Lepidoptera: Crambidae), was identified and recorded in cassava crops in these states.